Lightweight Vapor-Permeable Plasters for Building Repair Detailed Experimental Analysis of the Functional Properties - Záleská, Martina (Materials (Basel), 2021)
Three types of lightweight plasters for building repair were prepared and tested. The composition of plasters was designed in respect to their compatibility with materials used in the past in historical masonry. For the hardened plasters, detailed testing of microstructural and macrostructural parameters was realized together with the broad experimental campaign focused on the assessment of mechanical, hygric, and thermal properties. As the researched plasters should find use in salt-laden masonry, specific attention was paid to the testing of their durability against salt crystallization. The mechanical resistance, porosity, water vapor transmission properties, and water transport parameters of all the researched plasters safely met criteria of WTA directive 2-9-04/D and standard EN 998-1 imposed on repair mortars. Moreover, the tested materials were ranked as lightweight plasters and due to their low thermal conductivity they can be used for the improvement of thermal performance of repaired masonry. The salt crystallization test caused little or no damage of the plasters, which was due to their high porosity that provided free space for salt crystallization. The developed plasters can be recommended for application in repair of damp and salt masonry and due to their compatible composition also in historical, culture heritage buildings. The added value of plasters is also their good thermal insulation performance.